MODERASI BERAGAMA SEBAGAI PILAR KETAHANAN NASIONAL : STUDI KONSEPTUAL DAN EMPIRIS - Permatasari, Septi; Lilis Karyawati; Nur Aini Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Religious moderation is a strategic approach to maintaining social harmony and strengthening national resilience amidst Indonesia's diversity. This article examines the concept of religious moderation and its implementation within the context of national resilience through a literature study of various scholarly articles. The findings indicate that religious moderation plays a significant role in mitigating potential conflicts, preventing radicalism, and strengthening national identity. Effective implementation of religious moderation requires synergy among the government, religious leaders, and civil society. This article offers theoretical and practical contributions in supporting national policies based on the values of moderation.